Pregnancy Examination with Postpartum Hemorrhage: SDKI Data Analysis 2017 - Monika Sani Turnip; Sudijanto Kamso (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Postpartum haemorrhage is one of the leading causes of maternal mortality in Indonesia. Adequate pregnancy screening (Antenatal Care/ANC) plays a vital role in preventing and managing pregnancy complications, including postpartum bleeding. Objective: This study aims to analyze the relationship between pregnancy examination (ANC) and the incidence of postpartum bleeding based on data from the Indonesian Demographic and Health Survey (SDKI) 2017. Methods: This research method is quantitative observational analytic through cross-sectional techniques with research. Result: shows a relationship between quantity or frequency and the incidence of bleeding with a p-value of 0.05. However, there is no relationship with the quality of the pregnancy checkup (p-value 0.548). Even though it is not related, the quality of the pregnancy checkup has a risk of bleeding incidents with POR: 0.872 (CI 95%: 0.558-1.363), which means that mothers who do not receive services according to the 10T standard have a 1.3 times risk of bleeding during childbirth. Conclusion: Adequate pregnancy screening (ANC), both in terms of frequency and quality, plays a vital role in reducing the risk of postpartum bleeding. Efforts to improve access and quality of ANC should be a priority in maternal health programs in Indonesia.